Geobacter sulfurreducens Extracellular Multiheme Cytochrome PgcA Facilitates Respiration to Fe(III) Oxides But Not Electrodes - Zacharoff, Lori A.; Morrone, Dana J.; Bond, Daniel R. (Frontiers in Microbiology, 2017)
Extracellular cytochromes are hypothesized to facilitate the final steps of electron transfer between the outer membrane of the metal-reducing bacterium Geobacter sulfurreducens and solid-phase electron acceptors such as metal oxides and electrode surfaces during the course of respiration. The triheme c-type cytochrome PgcA exists in the extracellular space of G. sulfurreducens, and is one of many multiheme c-type cytochromes known to be loosely bound to the bacterial outer surface. Deletion of pgcA using a markerless method resulted in mutants unable to transfer electrons to Fe(III) and Mn(IV) oxides; yet the same mutants maintained the ability to respire to electrode surfaces and soluble Fe(III) citrate. When expressed and purified from Shewanella oneidensis, PgcA demonstrated a primarily alpha helical structure, three bound hemes, and was processed into a shorter 41 kDa form lacking the lipodomain. Purified PgcA bound Fe(III) oxides, but not magnetite, and when PgcA was added to cell suspensions of G. sulfurreducens, PgcA accelerated Fe(III) reduction similar to addition of FMN. Addition of soluble PgcA to ∆pgcA mutants also restored Fe(III) reduction. This report highlights a distinction between proteins involved in extracellular electron transfer to metal oxides and poised electrodes, and suggests a specific role for PgcA in facilitating electron transfer at mineral surfaces.